2015
DOI: 10.1007/978-981-287-420-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Alleviation with Microfinance: Bangladesh Evidence

Abstract: This study provides evidence of the impact of membership of a microfinance institution (MFI) in Bangladesh on poverty alleviation. Using a quasi-experimental approach with a control group the members of which had never been members of a MFI, interviews with members of a prominent Bangladesh MFI were conducted in relation to their material possessions. In almost every aspect of material well-being, including income, ownership of assets, savings and food intake, members of the MFI are significantly better off th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“… Ref. a Country Study design Group targeted b Intervention description Intermediate outcomes reported c Nutritional outcomes reported ( Nair et al, 2017 ) IN RCT BCC group BCC through a facilitated PLA cycle, home visits during pregnancy and early childhood None BMI, MUAC, nutrition wellbeing, diet diversity (woman); birthweight, HAZ, WHZ, WAZ, MUAC, stunting, wasting, underweight, exclusive BF, CF introduction, protein intake, diet diversity, minimum meal frequency (child) ( Harris-Fry et al, 2016 ) BG Quasi-experimental BCC group BCC through a facilitated PLA cycle None Diet diversity (woman) ( Tripathy et al, 2016 ) IN RCT BCC group BCC through a facilitated PLA cycle None Early BF initiation, exclusive BF ( Acharya et al, 2015 ) IN RCT BCC group BCC delivered by health worker on maternal and newborn health None Feeding colostrum, early BF initiation, exclusive BF ( Malapit et al, 2015 ) IN Cross-sectional Multiple/unspecified group NA; only measured impact of group membership Empowerment, production diversity BMI, HAZ, WAZ, WHZ, diet diversity (woman) ( Younes et al, 2015 ) BG Quasi-experimental BCC group BCC through a facilitated PLA cycle None Exclusive BF, diet diversity (child) ( Habib and Jubb, 2015 ) BG Cross-sectional Microfinance group NA; only measured impact of group membership Income Meals consumed per day (woman) ( ...…”
Section: Summary Of Evidence Relating Women's Group Programs To Nutrimentioning
confidence: 99%
See 1 more Smart Citation
“… Ref. a Country Study design Group targeted b Intervention description Intermediate outcomes reported c Nutritional outcomes reported ( Nair et al, 2017 ) IN RCT BCC group BCC through a facilitated PLA cycle, home visits during pregnancy and early childhood None BMI, MUAC, nutrition wellbeing, diet diversity (woman); birthweight, HAZ, WHZ, WAZ, MUAC, stunting, wasting, underweight, exclusive BF, CF introduction, protein intake, diet diversity, minimum meal frequency (child) ( Harris-Fry et al, 2016 ) BG Quasi-experimental BCC group BCC through a facilitated PLA cycle None Diet diversity (woman) ( Tripathy et al, 2016 ) IN RCT BCC group BCC through a facilitated PLA cycle None Early BF initiation, exclusive BF ( Acharya et al, 2015 ) IN RCT BCC group BCC delivered by health worker on maternal and newborn health None Feeding colostrum, early BF initiation, exclusive BF ( Malapit et al, 2015 ) IN Cross-sectional Multiple/unspecified group NA; only measured impact of group membership Empowerment, production diversity BMI, HAZ, WAZ, WHZ, diet diversity (woman) ( Younes et al, 2015 ) BG Quasi-experimental BCC group BCC through a facilitated PLA cycle None Exclusive BF, diet diversity (child) ( Habib and Jubb, 2015 ) BG Cross-sectional Microfinance group NA; only measured impact of group membership Income Meals consumed per day (woman) ( ...…”
Section: Summary Of Evidence Relating Women's Group Programs To Nutrimentioning
confidence: 99%
“…In a subsequent study, the authors found that the benefit on energy and protein intake was higher with longer group participation and greater initial poverty ( Deininger and Liu, 2013b ). Likewise, in a study in Bangladesh, compared to members of a microfinance program who had participated for four or eight years, non-participants were less likely to consume three meals per day ( Habib and Jubb, 2015 ).…”
Section: Summary Of Evidence Relating Women's Group Programs To Nutrimentioning
confidence: 99%
“…On the other hand, MFIs have been successfully working for poverty alleviation over the last few decades (Gonzalez & Rosenberg, 2006;Gutierrez-Nieto, Serrano-Cinca & Molinero, 2009;Habib & Jubb, 2015). Thus, academics and policymakers have been examining the relationship between these two opposite but significant objectives of MFIs operation-financial stability (also known as organizational motive) and depth of social outreach (Hermes, Lensink & Meesters, 2011;Im & Sun, 2015;Lafourcade, Isern, Mwangi & Brown, 2005).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Local experiences are, however showing a difficult universal application and what works in Bangladesh (Habib and Jubb, 2015) is not always successful in South America (Washington and Chapman, 2014) or in Sub-Saharan Africa (Moro Visconti, 2012), even if international cross-pollination plays a substantial role.…”
Section: Resultsmentioning
confidence: 99%